Effects of Calcium Supplementation on Glucose and Insulin Levels of Athletes at Rest and After Exercise - (:unkn) unknown (HUMANA PRESS INC, 2010)
This study was performed to determine how the calcium supplementation for a 4-week period affects the glucose and insulin levels at rest and at exhaustion in athletes. This is a 4-week study performed on 30 healthy subjects varying between 18 and 22 ages. Subjects were separated into three groups: first group (group supplemented with calcium, sedentary group), second group (calcium supplementations + exercise group), and third group (training group). Glucose and insulin parameters of the groups were measured four times, at rest and exhaustion in the beginning of the research and at rest and exhaustion after the end of 4 weeks application period. Exhaustion measurements both before and after the supplementations significantly decreased in compared to rest measurements in terms of insulin (p < 0.05). Significant difference was not determined in the glucose values of groups. In terms of glucose, values increased in all of the three groups occurred with exercise both before and after the supplementation by exercise and exhaustion (p < 0.05). The results of our study indicate that calcium gluconate supplementations for 4 weeks in sedentary subjects and athletes did not significantly affect plasma insulin levels at rest and exhaustion. However, glucose levels were affected by calcium supplementation and exhausting exercise in athletes.
Keywords: Exercise; Calcium supplementation; Insulin; Glucose